Ghana : Background Information on Output and Investment Performance. (IMF Staff Country Reports; Country Report ;, 1995)
This paper examines some factors that may have accounted for the investment and growth performance of Ghana during the past two decades, with special emphasis on the economic recovery program (ERP) period. The paper highlights that Ghana's growth performance responded well to the liberalization of the exchange and trade regime and the elimination of price controls. Sustained implementation of stabilization policies without reversals was also strongly supportive of growth. However, inflation remained relatively high-at about 25-30 percent-and unpredictable, dampening the incentives for the private sector to save and invest.